Legal aspects of sports - Miller, John J. (John James) 1956-; Schoepfer, Kristi L. (Jones & Bartlett Learning, 2018)
Legal Aspects of Sports, Second Edition provides an accessible introduction to the legal aspects of sports relevant to future sport managers and coaches, streamlined in such a way that emphasizes content most relevant to sport management. Using the foundation of Patrick K. Thornton's Sports Law, this text has been thoroughly revised to reflect the ever-evolving field of sports law, touching on such hot-button issues as discrimination and drug testing in sports. The Second Edition has also been completely reorganized to improve the flow of the material, beginning with a discussion of the role of sports in society and followed by coverage of torts, contracts, and a range of relevant topics. Case studies relevant to each chapter can now be found online and are accessible through the Navigate 2 platform.-- Publisher's description